(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article studies directions for implementing proactive budgeting in the Republic of Uzbekistan. Measures to be implemented to further improve proactive budgeting practices, additional tasks assigned to the accounts chamber and the state financial control inspectorate in proactive budgeting are analyzed. Scientific conclusions and recommendations are presented on the basis of analyses.